Reconstructing Paleofluid Circulation at the Hercynian Basement/Mesozoic Sedimentary Cover Interface in the Upper Rhine Graben - Chrystel Dezayes; Catherine Lerouge (Geofluids)
In this paper, we focus on paleocirculation at the Hercynian basement/sedimentary cover interface in the tectonic environment of the Upper Rhine graben. The goal is to increase our understanding of the behavior of the fracture-fault network and the origin of the hydrothermal fluids. We studied orientations, mineral fillings, and fluid origins of fractures that crosscut the Hercynian granitic basement and the Permo-Triassic formations in relation to the major tectonic events. Because the Mesozoic formations and the Hercynian basement on the graben flanks and inside the graben do not have the same evolution after uplift, our study includes 20 outcrops on both graben flanks and cores of the Soultz-sous-Forêts geothermal wells located inside the graben. The Hercynian granitic basement and Permo-Triassic formations were affected by several brittle phases associated with fluid circulation pulses related to graben formation during the Tertiary. We distinguished at least four stages: (1) reactivation of Hercynian structures associated with pre-rift tectonics during the early Eocene and descending meteoric waters, characterized by shearing/cataclasis textures and precipitation of illite and microquartz; (2) initiation of convective circulation of deep hot brines mixed with descending meteoric waters at the Hercynian basement/sedimentary cover interface during this first stage of Eocene rifting, characterized by dolomite and barite fillings in reactivated Hercynian fractures; (3) N-S tension fractures associated with rift tectonics just prior to uplift of the graben shoulders during Oligocene extension and descending meteoric waters, characterized by cataclastic textures and precipitation of quartz, illite, hematite, and barite; and (4) current convective circulation of deep hot brines mixed with descending meteoric waters at the Hercynian basement/sedimentary cover interface, characterized by calcite and barite fillings within the graben. This convective circulation is today present in deep geothermal wells in the western part of the Rhine graben.